Processo de angústia/sofrimento moral em enfermeiros da Estratégia Saúde da Família: cartografia da produção de subjetividades - Beatriz Santana Caçador (2016)
Changes in the political and organizational context in the world of work and health have produced paradigmatic reconfigurations and new ethical challenges. In family health, nurses construct their ways of doing health and their ways of being professional in a conflictive arena in which they dispute hegemonic practices and the possibility of creating the new one, of the invention of knowledges and actions that have the integral care as central axis . Thus, family health is a territory marked by ethical emblems that affect the professional practice of nurses, causing them to experience moral suffering. It is a qualitative study guided by the cartographic method, carried out in the metropolitan area of Belo Horizonte, whose objective was to analyze the process of moral distress / suffering in nurses in the context of family health, in light of the cartography of its subjectivation process. A total of 14 nurses from the Family Health Strategy participated in the study. Data collection took place through semi-structured script-guided interview. To organize the data, the Atlas Ti software was used and the data analysis was performed using a conceptual philosophical method. Five axes of reflection emerged: 1) The reconfiguration of the Conceptual Framework of analysis of the process of anguish / moral suffering in the light of the cartographic method of production of subjectivity; 2) The landscape of the research scenario, considering the organizational designs, management models and experiences of nurses' moral suffering through such agency; 3) The moral suffering related to the care practices imposed by the management, which are considered by the invasive and domineering nurses. 4) Experiences of moral suffering related to the advocacy role that the nurse performs and assumes as internal morality. 5) The polarity of the subjectivation process of family health nurses whose meanings transpire between acts of belonging about "being everything" and "being nothing". It is concluded that the process of moral distress / suffering of family health nurses and associated processes of subjectivation are produced amid the tensions and forces that dispute the production of care. The biomedical paradigm and management models based on clientelism produce ethical conflicts in the daily life of family health and participate in the subjective modulations of society. The principles of the SUS are understood by nurses as ethical values that provoke their force of desire, impelling them to create escape lines to resist the biopolitical context. At the same time, they perpetuate the established logic of health by moving through the demands of demand, without questioning them, assuming practices that escape their professional scope, weakening their recognition and social legitimacy. They experience moral anguish / suffering in this field and their subjective production transits the polarity of the meanings of "being everything" and "being nothing". In the midst of the ethical conflicts registered in family health, nurses construct their professional practice as well as their way of being subject, experiencing processes of moral suffering, reproduction of established care practices, invention and escape and also construction of new Territories.